2011
DOI: 10.1111/j.1474-919x.2011.01151.x
|View full text |Cite
|
Sign up to set email alerts
|

Differences in foraging ecology determine variation in visual fields in ibises and spoonbills (Threskiornithidae)

Abstract: Variations in visual field topography among birds have been interpreted as adaptations to the specific perceptual challenges posed by the species’ foraging ecology. To test this hypothesis we determined visual field topography in four bird species which have different foraging ecologies but are from the same family: Puna Ibis Plegadis ridgwayi (probes for prey in the soft substrates of marsh habitats), Northern Bald Ibis Geronticus eremita (surface pecks for prey in dry terrestrial habitats), African Spoonbill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 22 publications
(54 reference statements)
1
39
0
Order By: Relevance
“…Each species probably has a unique ''world view'' with respect to the overall sector of the world from which it can extract information at any one instant, while within that field of view there will be differences in the distribution of spatial resolution and of colour vision. It has been shown that these differences in world view may be correlated with significant differences in the foraging ecology and foraging behaviour of birds of the same genus (Guillemain et al, 2002), family (Martin and Portugal, 2011) or order (Martin and Prince, 2001). Thus generalisations across species groups, such as those listed in Tables 1 and 2 should be made with caution.…”
Section: Unique World Views and Their Limitsmentioning
confidence: 94%
See 1 more Smart Citation
“…Each species probably has a unique ''world view'' with respect to the overall sector of the world from which it can extract information at any one instant, while within that field of view there will be differences in the distribution of spatial resolution and of colour vision. It has been shown that these differences in world view may be correlated with significant differences in the foraging ecology and foraging behaviour of birds of the same genus (Guillemain et al, 2002), family (Martin and Portugal, 2011) or order (Martin and Prince, 2001). Thus generalisations across species groups, such as those listed in Tables 1 and 2 should be made with caution.…”
Section: Unique World Views and Their Limitsmentioning
confidence: 94%
“…Surprisingly, visual fields do not appear to be directly associated with the perceptual challenges associated with the control of locomotion; this seems to be achieved within the constraints imposed by other factors (Martin, 2012(Martin, , 2014. Differences in visual fields can be finely tuned and are known to occur between species within the same genus which differ in their foraging techniques (Guillemain et al, 2002), as well as within families (Martin and Portugal, 2011).…”
Section: Visual Fields and The Topography Of Visionmentioning
confidence: 96%
“…Thus, among the ibises (Threskiornithidae), significant differences in visual fields are found between species whose foraging ecology involves surface pecking in dry terrestrial habitats (northern bald ibis Geronticus eremita) and species which probe in the soft substrates of marsh habitats (puna ibis Plegadis ridgwayi) [15]. However, among the herons (family Ardeidae) within the Ciconiiformes, there is a marked similarity in visual field configurations even among species from different genera.…”
Section: (Iii) Congeneric and Intra-family Differences In Visual Fieldsmentioning
confidence: 99%
“…Therefore, determining a causal relationship between eye structure and behavioural function may be problematic. Nevertheless, subtle behavioural differences may provide a crucial underpinning to the partitioning of resources between species within the same or similar environments, and are thus likely to be reflected in aspects of sensory capacity and information processing [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…While some species search for food when flying at high altitude, others search from a perch or by walking on the ground (Del Hoyo and Elliot, 1994), and we suggest that raptor species with different foraging ecology might differ in their visual fields, eye and head movements (O'Rourke et al, 2010a,b) and perhaps in their visual acuity. Significant differences in the vision of closely related birds that differ in their foraging behaviour have been described in other species (Guillemain et al, 2002;Martin and Piersma, 2009;Martin and Portugal, 2011).…”
Section: Introductionmentioning
confidence: 99%